The African Continental Free Trade Area and Developmental Regionalism: Leveraging Transport Corridors to actualise the AfCFTA - Maneli, Sibusiso (Graduate School of Development Policy and Practice, 2024)
The AfCFTA is a significant opportunity for African countries to promote intra-Africa trade and long-term economic growth. However, a gargantuan obstacle to realising these ambitions is Africa's infrastructure deficit. Energy and transport infrastructure is essential for trade facilitation. Without the development of adequate, reliable and efficient infrastructure alongside soft infrastructure advances, the AfCFTA risks becoming a paper tiger. As such, the AfCFTA must be a developmental trade agreement – promoting the congruent development of soft, importantly, hard infrastructure to fulfil its promise of broadening and deepening economic integration. This thesis advocates that the AfCFTA should adopt a developmental approach to integration. In doing so, it highlights that the AfCFTA must operate within a developmental regionalism framework to coalesce member countries to cooperate on crossborder infrastructure development to improve trade facilitation. To this end, using the Maputo Development Corridor as a case study, this thesis highlights the importance of developmental economic corridors in improving cooperation on cross-border infrastructure development, and trade facilitation for the success of the AfCFTA.